Effect Warm Worldthe fluctuation of Temperature Iran under the Dynamic Model EH5OM - kamal Omidvar; reza ebrahimi; Mohammad kykhsrvy Kayani; ghasem lkzashkoor (تحقیقات کاربردی علوم جغرافیایی)
The aim of this study was to investigate the effects of global warming on where the slope changes when the monthly temperature in Iranian territory over the coming decades (2050-2015). The simulated temperature dynamic model EH5OM subset Hybrid Models atmospheric circulations (GCM) selection and data model of the Center for Theoretical Physics Salam (Italy) were derived from emission scenarios A1B scenario was chosen given the scenario of 2100 -2001 found that from 2050 to 2015 were used in this study data is then output the data in the fourth edition of the regional climate model (RegCM4) Linux environment was fine scale output data Downscaling model with dimensions of 27/0 * 27 / Degrees latitude is where the dimensions of 30 x 30 km area of ​​approximately cover the average temperature of the matrix deals 13140 2140 * was extracted. Finally, the slope of the average monthly temperature during the period under study by Mann-Kendall slope age and matrix computation in MATLAB software 13140 * 12 respectively. Results show rising temperatures in March and April to June, more than 90% of the country, that it will be spring's warmer. Increasing the temperature in the winter months and spring mountainous parts of the western half of the country is warming the cold regions of Iran. Temperature negative trend in October and November in the northern part of the eastern half of the region's countries could be indicative of colder temperatures in the northern West.